ANALISIS KECERDASAN INTERPERSONAL PESERTA DIDIK KELAS VII MTs NURUL ISLAM PONTIANAK BARAT - Saifudin, Saifudin; Wicaksono, Luhur; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractInterpersonal intelligence is the ability of students in their efforts to give a good impression about themselves, trying to balance themselves with the environment, controlling feelings and being able to express reactions with time and conditions so that interactions with others can be intertwined smoothly and effectively. Therefore, researchers want to examine the Interpersonal Intelligence Analysis of Class VII MTs Nurul Islam West Pontianak students so that researchers are expected to obtain accurate information regarding the Interpersonal Intelligence Analysis of Class VII MTs Nurul Islam Pontianak Barat students.The method used in this research is descriptive method because it explains about social interaction in VIIMTs Nurul Islam West Pontianak students. The sample of this study was 30 students of VII grade MTs Nurul Islam, West Pontianak. This research uses indirect communication techniques using tools such as questionnaires or questionnaires. Questionnaire is intended for students to find out how much students' understanding of the material that has been delivered and given to students. This research is a quantitative approach because in analyzing the data the descriptive statistical technique is used..Â Keywords:Interpersonal Intelligence